(untitled) (World Bulletin of Public Health, 2026)
This article provides a comprehensive analysis of cardiac arrhythmias and the clinical and pharmacological characteristics of antiarrhythmic drugs used in their treatment. Arrhythmias arise as a result of disturbances in the heart rhythm and conduction system and manifest with varying degrees of clinical symptoms. In modern medicine, antiarrhythmic agents are considered one of the main tools for normalizing heart rhythm. In particular, the specific features of their use in both children and adults highlight their clinical significance. Therefore, this article discusses the pharmacodynamics, pharmacokinetics, indications for use, adverse effects, and the importance of an individualized approach to therapy. It also substantiates that the patient’s general condition, underlying diseases, and the type of arrhythmia are key factors in selecting appropriate treatment in clinical practice.